解析設計研究法的架構與實施：以科學教育研究為例 Exploring the Framework and Implementation of the Design Research Method in Science Education - 許瑛玿 Ying-Shao Hsu; 莊福泰 Fu-Tai Chuang; 林祖強 Tzu-Chiang Lin (National Taiwan Normal University, 2012)
近年來，教育研究者著力於發展出可以應用在實務現場的理論，並倡議研究時系統性分析實務現場的研究資料，藉以建立教學設計和教育理論間的關聯，進而改進教學。因應上述的風潮，學者提出了設計研究法，此新興研究法的優點是能針對有理論基礎的設計進行深入研究，透過多次的循環歷程精緻化設計，進而修改原來的理論或發展原形理論。本文詳細介紹設計研究法的四大特性：一、經落實有理論基礎的設計於實務來檢視理論的適用性或提出原形理論；二、詳實紀錄研究歷程與系統中的互動情形；三、具有循環修正的歷程並彰顯修正過程的價值；四、運用系統性分析探討不同層次間的交互作用。再分析30 篇發表於SSCI期刊科學教育相關的實徵論文來探索設計研究法的實施步驟，並輔以實例說明如何實施設計研究法。最後，進一步指出設計研究法與其他研究法的異同，以及應用設計研究法於教育研究上所面臨的一些限制，試圖釐清設計研究法的架構和具體的實施步驟，以作為未來檢視創新教學成效的另一種可以考慮採行的研究法。 In recent years, educators have explored the relationships between instructional designs and educational theories by systematically analyzing research data to improve teaching quality. Therefore, the design research method was proposed to enable researchers to modify an original theory or develop a prototype theory by sophisticating the design of cyclic procedures through repeated trials. This study explicates the features of the design research method, such as (1) examining the appropriateness of theories or proposing prototype theories by implementing theory-based designs into practice; (2) maintaining records of the research process and within system interactions; (3) featuring and emphasizing the value of cyclic processes; and (4) systematically analyzing interactions between various levels. Using the 30 collected studies published in SSCI journals, this study explores the steps involved in implementing the design research method. Furthermore, this study also discusses the homogeneity and heterogeneity between the design research and other research methods and the limitations of applying the design research method to research in the educational field. By clarifying the characteristics and implementation procedures of the design research method, the possibility of applying the design research method to educational research for innovative designs is enhanced.